The relationship between mothers' knowledge level and the environment with the incidence of ARI in children aged 1-5 years at Lubuk Kilangan Health Center - Sri Wahyuningsih (PT WIM Solusi Prima, 2026)
ISPA is the most common disease suffered by toddlers, namely 78% of toddlers come to health services with ISPA incidents every year, the number of toddlers treated with ISPA incidents is 42.91%. Based on routine reports from the ISPA Sub-Directorate, the ISPA incident is 20.06% in Indonesia and the ISPA incident rate in West Sumatra according to the 2023 Indonesian Health Profile was found to be 29.9%. ISPA cases at the Lubuk Kilangan Health Center in 2024 were found to be 2,319 cases. The purpose of this study was to determine the relationship between the level of maternal knowledge and the environment with the incidence of acute respiratory infections (ARI) in toddlers aged 1-5 years at the Lubuk Kilangan Health Center. This type of research is quantitative with a cross-sectional approach conducted at the Lubuk Kilangan Health Center on February 17-22, 2025. The population of this study was 368 with a sample of 79 using the accidental sampling technique. Data collection using questionnaires, analyzed univariately and bivariately using the Chi-Square test p < 0.05. The results of the Chi-Square test of the relationship between the level of knowledge and the incidence of ISPA in toddlers showed ρ-value = 0.000 < 0.05. More than half of toddlers live in a non-risk environment (95%), more than half of toddlers are exposed to cigarette smoke (91%). The conclusion is that there is a relationship between the level of maternal knowledge and the incidence of ISPA at the Lubuk Kilangan Community Health Center. It is expected that the health center can improve health education for mothers of infants as well as efforts to improve the environment in order to reduce the incidence of ARI in children aged 1–5 years.